NARASI MEDIA ONLINE TERKAIT AKSI DEMOKRASI 2025 SEBAGAI REPRESENTASI KOMUNIKASI POLITIK - Yuli Amelia; Ida Riaeni (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
The 2025 Democracy Action (Action Demokrasi 2025) is one of the biggest political phenomena in Indonesia, giving rise to demands for the dissolution of the House of Representatives (DPR) and reflecting a crisis of public trust in legislative institutions.Amidst the rapid flow of digital information, online media plays a crucial role in framing this issue and shaping public perceptions of political legitimacy and democracy. This study aims to analyze how online media construct news narratives about the 2025 Democracy Action and how the representation of political communication reflected in these narratives influences public perceptions of political legitimacy in Indonesia. This study uses a descriptive qualitative method with a critical discourse analysis approach (Critical Discourse Analysis) model by Teun A. van Dijk. Data were obtained from news articles from national online media such as Kompas.com, Detik.com, Tempo.co, and CNN Indonesia during the period January- August 2025. The results indicate differences in reporting methods between media. The narratives conveyed by Tempo.co and CNN Indonesia emphasize public participation and the crisis of legitimacy, while Kompas.com and Detik.com direct more attention to issues of national security and stability. These differences in emphasis reflect ideological orientations that influence how news is structured and impact public understanding of democracy and levels of public trust in political institutions. In this context, online media functions not merely as a channel for conveying information but also as an agent shaping political reality and public perceptions of the legitimacy of democracy in Indonesia. Keywords: Democracy Action 2025, framing, political communication, democratic legitimacy, online media.